PhyloFunDB: A Pipeline to Create and Update Functional Gene Taxonomic Databases - Ohana Y. A. Costa; Mattias de Hollander; Eiko E. Kuramae; Paul L. E. Bodelier (Microorganisms, 2022)
The increase in sequencing capacity has amplified the number of taxonomically unclassified sequences in most databases. The classification of such sequences demands phylogenetic tree construction and comparison to currently classified sequences, a process that demands the processing of large amounts of data and use of several different software. Here, we present PhyloFunDB, a pipeline for extracting, processing, and inferring phylogenetic trees from specific functional genes. The goal of our work is to decrease processing time and facilitate the grouping of sequences that can be used for improved taxonomic classification of functional gene datasets.